Perilaku Narsistik Remaja di Media Sosial dan Implikasinya bagi Bimbingan dan Konseling - Saripah, Ipah; Albari, Muhammad Ridho; Pratiwi, Tiara Iskandar; Nadhirah, Nadia Aulia (Indonesian Journal of Educational Counseling, 2023)
The increasing use of social media has several impacts, including the emergence of narcissistic behavior in adolescents. Narcissistic behavior in adolescents on social media is freely spreading identity and what happened to them, spreading other people's secrets or disgrace on social media, leaving negative comments on other people's social media, and wanting other people on social media to know what they have. This study aims to determine the tendency of adolescent narcissistic behavior on social media. This research uses a literature study method. Ease of access to using social media is one of the factors in the phenomenon of narcissism that occurs, especially among adolescents. Guidance and counseling services that can be developed related to narcissism are use guidance groups.